Pengembangan Media Pembelajaran PPT Interaktif Berbasis Canva pada Tema Norma di dalam Masyarakat di Kelas IV SD Negeri 79 Palembang - Maulani, Meva; Arni, Yusni; Mariska, Revi; Utami, Feriska (Pusdikra-Publishing.com, 2025)
This study aims to produce canva-based learning media used in Pancasila Education subjects taught in grade IV of SD Negeri 79 Palembang using the Canva application. For this study, the ADDIE development model was used which consists of five stages of analysis, design, development, implementation, and evaluation. At the analysis stage, namely identifying student needs, learning tools, and curriculum. The selection and creation of the canva design is part of the design stage. At the development stage, researchers developed canva by combining images, text, and other interesting elements. Implementation was carried out by using canva in learning activities to test how effective the media was. The final evaluation of the development of digital canva regarding norms in society in grade IV of SD Negeri 79 Palembang showed the effectiveness of this media in increasing student understanding, learning engagement, and its visual appeal. The evaluation results are the basis for improvements so that canva better supports effective and enjoyable learning.